Pengaruh Inovasi Produk, Word of Mouth, dan Social Media Marketing, terhadap Keputusan Pembelian : Studi di Lembaga Kursus Bahasa Inggris Global English Pare - Cacun Havana; Zaenul Muttaqien; Ahmad Jauhari (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study was conducted with the motivation to analyze the impact of product innovation, word-of-mouth (WOM), and social media marketing on purchasing decisions at one of the English language courses located in Kampung Inggris, Pare, Kediri, namely Global English. In the digital era and increasingly fierce competition among non-formal educational institutions, understanding the factors that influence purchasing decisions is very important. This study used a quantitative approach with a survey method via Google Form, which was distributed to active students at the institution. The research instrument, a closed questionnaire, was designed to measure students' perceptions of the product innovation offered, the influence of word-of-mouth communication, and the effectiveness of marketing strategies through social media. The analysis results show that product innovation has a significant influence on purchasing decisions, particularly in terms of offering new programs that are in line with market needs, such as the "Studycation" program that combines learning and recreation. Word-of-mouth has also been shown to play an important role in building trust among potential consumers through positive experiences from previous users. In addition, social media marketing makes a real contribution to reaching a wider audience, increasing interaction, and strengthening the institution's image in the public eye. These three variables, both partially and simultaneously, had a positive and significant influence on purchasing decisions. These findings indicate that integrated, digital-based marketing strategies are key to attracting and retaining consumer interest in the informal education sector. This research is expected to serve as a reference for course providers and other educational institutions in designing innovative, efficient, and adaptive marketing strategies to address changing consumer behavior in the digital era.